2013
DOI: 10.1541/ieejeiss.133.1820
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Brain Temperature Distribution in Mathematical and Solid Models of Head Thermal Characteristics

Abstract: SUMMARY Accurate temperature control of brain tissue during hypothermia treatment is necessary in order to prevent secondary brain damage and to avoid various side effects. Thus, the visualization of the intracerebral temperature distribution in hypothermia treatment was studied at the fundamental level. For this purpose a virtual reality technology was used to create a mathematical model that reflects metabolic heat production and Fourier heat conduction in a brain with the necessary parameters based on vario… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 11 publications
2
5
0
Order By: Relevance
“…12, studies using mathematical models with continuous arrangement of regular tetrahedrons [1,13,14], same as in the present study, showed relatively good agreement between simulated and measured results for different algorithms of temperature control. 12, studies using mathematical models with continuous arrangement of regular tetrahedrons [1,13,14], same as in the present study, showed relatively good agreement between simulated and measured results for different algorithms of temperature control.…”
Section: Utility Of Simulations Using Regular Tetrahedral Coordinate supporting
confidence: 79%
See 4 more Smart Citations
“…12, studies using mathematical models with continuous arrangement of regular tetrahedrons [1,13,14], same as in the present study, showed relatively good agreement between simulated and measured results for different algorithms of temperature control. 12, studies using mathematical models with continuous arrangement of regular tetrahedrons [1,13,14], same as in the present study, showed relatively good agreement between simulated and measured results for different algorithms of temperature control.…”
Section: Utility Of Simulations Using Regular Tetrahedral Coordinate supporting
confidence: 79%
“…The proposed method was verified for dynamic models [1,2,9] and thermodynamic models [10,13,14]; the method combines a number of features advantageous for a wide variety of biomathematical simulations. Besides, continuous state distributions can be visualized because most of space is defined as computable domain.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations